2020
DOI: 10.1111/cpf.12659
|View full text |Cite
|
Sign up to set email alerts
|

Postactivation performance enhancement: Does conditioning one arm augment performance in the other?

Abstract: A proposed method for enhancing muscle strength is the utilization of postactivation potentiation. Postactivation potentiation is the phenomenon by which muscle force is increased following a conditioning activity/contraction (Burke, Rudomin, & Zajac, 1976; Young, Jenner, & Griffiths, 1998). This form of activity-dependent potentiation phenomenon is cited throughout the literature as staircase treppe, post-tetanic potentiation, postactivation potentiation and/or postactivation performance enhancement (Blazevic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Two prior studies whose intention was to investigate contralateral effects of a unilateral conditioning exercise reported potentiation of the conditioned leg but significant deficits with the homologous, contralateral limb (Andrews et al, 2016) or no contralateral effect (Wong et al, 2020) respectively. Wong et al (2020) used a 6-second MVIC as the conditioning stimulus and reported PAPE effects with the conditioned limb but not crossover effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two prior studies whose intention was to investigate contralateral effects of a unilateral conditioning exercise reported potentiation of the conditioned leg but significant deficits with the homologous, contralateral limb (Andrews et al, 2016) or no contralateral effect (Wong et al, 2020) respectively. Wong et al (2020) used a 6-second MVIC as the conditioning stimulus and reported PAPE effects with the conditioned limb but not crossover effects.…”
Section: Discussionmentioning
confidence: 99%
“…Two prior studies whose intention was to investigate contralateral effects of a unilateral conditioning exercise reported potentiation of the conditioned leg but significant deficits with the homologous, contralateral limb (Andrews et al, 2016) or no contralateral effect (Wong et al, 2020) respectively. Wong et al (2020) used a 6-second MVIC as the conditioning stimulus and reported PAPE effects with the conditioned limb but not crossover effects. Andrews et al (2016) used Bulgarian split squats (5 repetitions at 50% of 1-repetition maximum [1RM], 2 repetitions at 70% 1RM and 1 repetition at 90% 1RM with 3-min rest periods between sets) as the conditioning exercise and found post-intervention deficits to the countermovement jump and no change to the DJ in the contralateral limb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some authors investigated the acute non-localized effects of both upper and lower body resistance exercises. Wong et al [8] and Andrews et al [9] investigated the acute effects of a monolateral exercise session for the upper body on the contralateral arm. No non-localized PAPE, however, were detected in these studies.…”
Section: Introductionmentioning
confidence: 99%